Assessing the Water Supply Potential of Boreholes on Kwame Nkrumah University of Science and Technology Campus - Boakye, Opoku Richard (2013)
A Thesis Submitted to the Department of Civil Engineering, Kwame Nkrumah University of Science and Technology in Partial Fulfilment of the Requirements for the Degree of Master of Science in Water Supply and Environmental Sanitation,